Association between N142D genetic polymorphism of GSTO2 and susceptibility to colorectal cancer - Masoudi, Mohammad; Saadat, Iraj; Omidvari, Shahpour; Saadat, Mostafa (Molecular biology reports, 2011)
Expression pattern analysis has been revealed that glutathione S -transferase omega 2 (GSTO2, a member of class omega) is ubiquitously expressed. Over expression of GSTO2 induced apoptosis. The gene encoding GSTO2 was localized to human chromosome 10q24.3, a region that may harbor gene(s) involved in the developing of colorectal cancer. To investigate the association between GSTO2 N142D genetic polymorphism and susceptibility to colorectal cancer the present study was done. We studied 63 (26 females, 37 males) colorectal cancer patients and 126 (52 females, 74 males) healthy individuals. The control subjects were frequency matched for age and gender with the colorectal cancer group. The genotypes were performed using RFLP-PCR method. The ND and DD genotypes were not associated with risk of colorectal cancer, in comparison with the NN genotype. Family history for cancer in the first degree of relatives significantly differed between cases and controls ( P = 0.012). The profiles of GSTO2 genotypes and family history in control and cancerous groups were compared to each other. Subjects with NN genotype and positive family history significantly were at high risk to develop colorectal cancer in comparison with subjects with DD or ND genotypes and negative family history ( P = 0.003). Present findings indicating that GSTO2 NN genotype increase the risk of colorectal cancer in persons with positive family history for cancer in the first degree relatives.